Contribution au développement d’un modèle heuristique des temporalités en contexte de réchauffement climatique - Matthieu Le Duff; Gaëlle Lefer-Sauvage; Miki Mori (Temporalités)
This article is based on an example of social science climate change research in Mayotte, where researchers are unable to understand the answers given by the respondents due to a cultural misunderstanding when trying to talk about climate change. The focus on climate change serves as a vector to more broadly address how researchers might understand, define and model the construction of time in Mayotte. First, we propose an epistemological approach to the construction of time, which we have coined the Chronoglyph. The Chronoglyph, whether thought of on a collective or individual scale, refers to the distribution of four “elementary patterns” known as “temporal dimensions,” which together constitute time. The subtlety of these notions and “temporal dimensions” are discussed, based on the work of Hartog (2003, 2020, 2022), Philippson (1949), Chesneaux (1996) and Dubar (2014). Next, we test the validity and robustness of our modeling of temporal dimensions and the dynamics they produce by analyzing two cultural conceptions of time in Mayotte: the notion of Umri (Blanchy, 1988) and the Shungu ceremony (Lambek, 2018). Through a discursive analysis of anthropological writings about Mayotte, we confirm the presence of the four temporal dimensions in the Maore (from Mayotte) model of time representation, before highlighting grey areas found in previous analyses. This first contribution on the construction of time in Mayotte has enabled us to generate methodological proposals for cultural research, such as with discursive analysis, and to propose new research linked to Descola's (2005) regimes of mondiation and to the meaning given to the regimes of historicity proposed by Hartog (2003, 2020, 2022).